2008
DOI: 10.1111/j.1532-950x.2008.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Fragmentation in the Synovial Pad of the Fetlock in Warmblood Horses

Abstract: Large synovial pad fragments in Warmblood horses can be associated with synovial and cartilage abnormalities, but further studies are warranted to determine their origin and clinical importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Declercq et al (2009) reported on fragmentation of the dorsal margin of the proximal phalanx in young Warmblood horses in which the majority underwent surgery for prophylactic reasons or to remove radiologic blemishes, or both. Osteochondral fragments within the dorsal plica have also been reported in Warmblood horses (Declercq et al, 2008). Impact fractures of the proximal phalanx in a filly have been described by Cullimore et al (2009) and the authors of this text have also seen similar lesions in the distal metacarpus.…”
Section: Arthroscopic Surgery In the Horse-advances Since 2005mentioning
confidence: 54%
“…Declercq et al (2009) reported on fragmentation of the dorsal margin of the proximal phalanx in young Warmblood horses in which the majority underwent surgery for prophylactic reasons or to remove radiologic blemishes, or both. Osteochondral fragments within the dorsal plica have also been reported in Warmblood horses (Declercq et al, 2008). Impact fractures of the proximal phalanx in a filly have been described by Cullimore et al (2009) and the authors of this text have also seen similar lesions in the distal metacarpus.…”
Section: Arthroscopic Surgery In the Horse-advances Since 2005mentioning
confidence: 54%
“…Although chondral fragments are known to survive in an intra-articular environment because they are permeated by nutrient synovial fluid [21], this is not well established for bony fragments. Therefore, at 3 months from its detachment, we cannot exclude that the osteochondral fragment contained remodeling or disrupted trabecular bone [22,23]. However, once the fragment is fixed, this thin bony part is considered to be quickly resorbed by creeping substitution [4].…”
Section: Discussionmentioning
confidence: 99%
“…These have been described by Declercq et al (2008). The relationship (if any) between the two conditions has not yet been determined.…”
Section: Osteochondral Fragments In the Dorsal Plicamentioning
confidence: 99%
“…The relationship (if any) between the two conditions has not yet been determined. Declercq et al (2008) reported fragments in the dorsal plica (proximal synovial pad) of 127 joints in 104 Warmblood horses; 20 horses had 2, 1 horse had 4, and the remainder had 1 joint affected. Fifty (40%) were in forelimbs and 77 (60%) were in hindlimbs.…”
Section: Osteochondral Fragments In the Dorsal Plicamentioning
confidence: 99%